Korelasi Antara Lama Menjalani Pengobatan Tuberkulosis Paru Dengan Skor Depresi Pada Pasien Tuberkulosis Paru Yang Menjalani Pengobatan di Poliklinik Paru RSUD Dr. Pirngadi Medan - Masdiwani noviana simanjuntak; Ade Pryta Simaremare; Rosminta Girsang (Universitas HKBP Nommensen, 2021)
Background : Pulmonary tuberculosis is an infectious disease caused by mycobacterium tuberculosis. This bactery can be transmitted through airbone particles and droplets. The treatment is a long term therapy and can be a stressor which effect patient’s physical and psychologycal, that leads to depression. Objective : The objective of this study was to determine the correlation between pulmonary tuberculosis treatment duration and depression score. Methods : This study was a correlative analysis with cross sectional design. The sample were 52 respondents whom currently endured the treatment of pulmonary tuberculosis in pulmonary unit in RSUD Pirngadi Medan, selected by consecutive sampling. Beck’s inventory depression II questionnaires were used to measure depression score. The data were analyzed with pearson correlation test. Result : There was a low negative correlation between duration of pulmonary tuberculosis treatment and depression score (p = 0,027 ; r = -0,309) Conclusion : The longer duration of pulmonary tuberculosis treatment, the lower the depression score.